Gambaran Pelaksanaan Serah Terima Antar Shift di Rumah Sakit X Jakarta - Amalia Cahyaningtyas; Hanny Handayani; Aat Yatnikasari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
A description of handover processes in hospital: A survey from Jakarta, IndonesiaBackground: Handover at the change of nurse shift is one of an important role in patient safety and continuiting quality of care.Purpose: To optimization of implementation of handover processes in hospital: A survey from Jakarta, IndonesiaMethod: An analysis study with approach fishbone diagram, start with filling in questionnaires, observations and interviews and then analyzed using fishbone diagrams. Based on fishbone diagrams, the problem was obtained that the implementation of handover of patient patients was not optimal.Results: To optimize the implementation of handover, implementation was carried out in the form of improving SPO, improving nurses' effective communication with SBAR and making role play video handover.Conclusion: The result is the handover can be optimal with the role and function of management of the head nurse especially a directing role. Recommendations given by follow up and revising the hand over standars, make a pilot project nursing ward and evaluate the implementation of the patient's handover through regular supervision.Keywords: Fishbone Diagram; Handover; Head Nurse; Optimization; DirectingPendahuluan: Serah terima perawat antar shift jaga merupakan salah satu komponen penting dalam mencapai keselamatan pasien dan mempertahankan kualitas asuhan.Tujuan: Meningkatkan optimalisasi fungsi pengarahan kepala ruang dalam pelaksanaan serah tertima antar shift di RS X Jakarta.Metode: Menggunakan study analysis situasi dengan pendekatan diagram tulang ikan, dimulai dengan mengisi kuesioner, observasi dan wawancara dan kemudian dianalisis menggunakan diagram tulang ikan. Berdasarkan diagram tulang ikan, masalah diperoleh bahwa pelaksanaan serah terima pasien pasien belum optimal.Hasil: Untuk mengoptimalkan pelaksanaan serah terima, implementasi dilakukan dalam bentuk meningkatkan SPO, meningkatkan komunikasi efektif perawat dengan SBAR dan membuat role play video serah terima.Simpulan: Hasilnya adalah serah terima dapat dioptimalkan dengan peran dan fungsi manajemen kepala ruang khususnya fungsi pengarahan. Rekomendasi yang diberikan dengan menindaklanjuti dan merevisi SOP serah terima, membuat ruang percontohan dan mengevaluasi pelaksanaan serah terima pasien melalui pengawasan rutin.